Optimization of Carrageenan extraction from Red algae (Acanthophora spp.) using response surface methodology )RSM). - Ynion, Thea Faye B.
Acanthophora spp. is an unexploited carrageenophyte in the Philippines with promising biotechnological properties. Studies on the polysaccharides from this red alga are scarce so optimization of the extraction process needs to be streamlined. Using Central Composite Design (CCD) of RSM, the interactions of extraction temperature (65-85℃), reaction time (2-3 h), and KOH concentration (3-6%) were explored. Optimum extraction conditions were designed based on yield (%), galactose (GAL, %), 3,6-anhydro-D-galactose (3,6-AG, %), and total suphate (%) contents. Results showed that optimum conditions for yield (30.84%) and suphate content (46.40%) was observed at 3% KOH concentration at 65°C for 2 h. 3,6-AG (1.9%) was detected highest at 6% KOH concentration at 65℃ for 2 h. Desirability of all responses obtained 0.940 which is close to 1 when KOH concentration is minimized, temperature is maximized and the time is in range. These designing conditions can be applied for carrageenan extraction to have higher yield and higher value of it chemical composition.